Development of Product Service System Modelling in SMED: The Case of Inventory Control - Samsiah, Suaily; Siti Zubaidah, Ismail (Penerbit UMP, 2018)
Development of Product Service System (PSS) in Small and Medium Enterprise Development (SMED) has been growing rapidly in the manufacturing industries. PSS is a combination between product and service in one system. Off ering a PSS in a manufacturing requires effective inventory control. However, for manufacturing company increased focus on inventory control on PSS means new challenges because PSS inventory is not only created through the physical products, but also with services. The research carried out involved proposing generic model using IDEF0 and evaluate the generic model development using Enterprise Dynamics Simulation (EDS).